Analisis Kualitas Layanan Aset Jalur Pedestrian di Jalan Astanaanyar Berdasarkan Konsep Walkability (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2026)
Pedestrian paths play an important role in supporting mobility, safety, and comfort for pedestrians in urban areas. However, on Astanaanyar Street in Bandung, pedestrian path facilities are considered suboptimal, especially in terms of comfort and safety. The issues identified include damaged or missing sidewalks at certain points, physical obstacles such as utility poles and street vendors, and a lack of supporting facilities and safe crossings. This study aims to evaluate the quality of pedestrian infrastructure assets on Astanaanyar Street based on six key dimensions of the walkability concept: connectivity, convenience, comfort, conviviality, conspicuousness, and coexistence. This study uses a descriptive method with a quantitative and qualitative approach, where data is obtained through questionnaires distributed to 152 users, field observations, and documentation studies. Data analysis is conducted using descriptive statistics to assess user perceptions and the existing conditions of pedestrian paths. The results of the study indicate that the quality of pedestrian path services on Astanaanyar Street is generally adequate, with poor scores in the dimensions of connectivity, comfort, and conviviality due to physical barriers and a lack of accessibility facilities. Meanwhile, the dimensions of convenience, conspicuousness, and coexistence received adequate scores, although they still require improvement. Therefore, an integrated redesign of the pedestrian path, infrastructure improvements, and enhancements to disability-friendly facilities and social elements are crucial to creating a safe, comfortable, and attractive public space while enhancing overall walkability along Astanaanyar Street.